2015
DOI: 10.3390/w7084427
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land Use on Surface Water Quality in a Subtropical River Basin: A Case Study of the Dongjiang River Basin, Southeastern China

Abstract: Abstract:Understanding the relationship between land use and surface water quality is necessary for effective water management. We estimated the impacts of catchment-wide land use on water quality during the dry and rainy seasons in the Dongjiang River basin, using remote sensing, geographic information systems and multivariate statistical techniques. The results showed that the 83 sites can be divided into three groups representing different land use types: forest, agriculture and urban. Water quality paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
103
4
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 57 publications
(63 reference statements)
9
103
4
4
Order By: Relevance
“…Sub-class dense settlements ratio was higher in the Mekong watershed with annual rainfall (median) of 1051 mm [36]. Precipitation exacerbated the deterioration of surface waters due to high overland flow in dense settlements [63].…”
Section: Impacts Of Terrestrial Determinants On Cewqmentioning
confidence: 99%
See 2 more Smart Citations
“…Sub-class dense settlements ratio was higher in the Mekong watershed with annual rainfall (median) of 1051 mm [36]. Precipitation exacerbated the deterioration of surface waters due to high overland flow in dense settlements [63].…”
Section: Impacts Of Terrestrial Determinants On Cewqmentioning
confidence: 99%
“…Few studies have shown that forest land cover has a positive relation with nitrogenous materials [47,74,75]. It could be attributed to higher water discharge and lower water residence time, which affects the uptake capacity of vegetation [63]. Populated forests with human intrusion (mean population density of 3 persons/km 2 ) and a higher annual rainfall of 1090 mm, were in higher ratio at the Mekong watershed compared to remote forests.…”
Section: Impacts Of Terrestrial Determinants On Cewqmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, all the nutrient parameters in this river were much higher than those of the others. This was closely connected with the high intensity of human activities [24]. Large amounts of incompletely treated sewage (e.g., municipal wastewater and industrial effluent) are discharged into the rivers, which is a problem in tropical Asian watersheds with dense populations and industries [39].…”
Section: The Patterns Of Variation Of the Phytoplankton Communities Imentioning
confidence: 99%
“…Although there are several large reservoirs in the basin, the hydrology and water availability of the basin still demonstrate strong seasonal variations [23]. The Li River, Qiuxiang River and Danshui River are three tributaries of the Dongjiang River and are respectively located upstream, midstream and downstream of the Dongjiang River [24]. The Li River originates from Liyuan Town and is approximately 100 km long.…”
Section: Study Areamentioning
confidence: 99%